Old age or better age? Ethical dilemmas - da Silva Santana, Carla (O Mundo da Saúde, 2012)
The experience of aging is always paradoxical, marked by dilemmas and, as a process it refers to the experience of time. Old age as “the best age” can only be compared with itself, when we establish points of reference from where the comparison would begin or when we compare it to the experience of others, which we observe and have some experiences in common. World population aging made us face a great challenge, the one of adding quality of life to additional years of life. Although there were many conquests and changes old people in developed countries have attained, there are still a long way to go in Brazil as regards old age as one of the best phases of life, all differences and peculiarities typical of each stage of life considered.